Coupling land surface and crop growth models for predicting evapotranspiration and carbon exchange in wheat-maize rotation croplands - D. Yang, H. Lei; Lokupitiya, E.; Shen, Y. (Copernicus Publications on behalf of the European Geosciences Union., 2010)
The North China Plain is one of the key crop-producing regions in China. However, water resources in the area are limited. Accurate modeling of water consumption and crop production in response to the changing environment is important. To describe the two-way interactions among climate, irrigation, and crop growth better, the modified crop phenology and physiology scheme from the SiBcrop model was coupled with the second version of the Simple Biosphere model (SiB2) to simulate crop phenology, crop production,and evapotranspiration of winter wheat and summer maize,which are two of the main crops in the region. In the coupled model, the leaf area index (LAI) produced by the crop phenology and physiology scheme was used in estimating sub-hourly energy and carbon fluxes. Observations obtained from two typical eddy covariance sites located in this region were used to validate the model. The coupled model was able to accurately simulate carbon and energy fluxes, soil water content, biomass carbon, and crop yield, especially for latent heat flux and carbon flux. The LAI was also well simulated by the model. Therefore, the coupled model is capable of assessing the responses of water resources and crop production to the changes of future climate and irrigation schedules of this region.